Initial assessment of triplex PCR assay application for detection of toxic dinoflagellates, Alexandrium species (Dinophyceae), in environmental samples - Van Helmond, Z (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves. 23-28).